Language ability and entrepreneurship education: necessary skills for Europe’s start-ups? - Johnstone, Leanne (2021)
Language ability and entrepreneurial education are seen as essential resources for start-ups operating in intensified landscapes of internationalisation and globalisation. Deemed as the necessary skills for corporate effectiveness vis-à-vis rivals, this paper responds to calls for increased understandings of cultural components as vital to entrepreneurship and the product of institutional forces. Thus, it explores (a) the impact language ability has on start-up expansion; (b) the perceptions of international relations as based on language ability as a tool for cross-cultural communication; and (c) the role of educational context from the entrepreneurs’ perspective. Based on interviews from European online start-ups across three discrete contexts—Finland, Portugal and Sweden—it concludes that contextual trends regarding language and education are founded upon the cultural-cognitive and normative pillars of institutionalisation. Further, by combining actor-context perspectives, it poses that language ability and education are resources borne from the domestic environment which positively moderate the start-up’s international success. Nevertheless, the notion of learnt entrepreneurship remains contested. Taken together, this study contributes by offering deeper insight into the role of context on entrepreneurial tendencies by combining resource and institutional perspectives.